Cobalt-doped nickel-molybdenum bimetallic phosphide grown on carbon cloth in situ as well as preparation method and application of cobalt-doped nickel-molybdenum bimetallic phosphide

By growing in situ on the carbon cloth and phosphated at high temperature, the cobalt-doped nickel-molybdenum bimetallic oxide is solved, and the structural instability of nickel-molybdenum bimetallic phosphide is achieved under fast charging and discharge, and higher rate performance and electrochemical stability are achieved. It is suitable for flexible supercapacitor positive electrode materials.

CN119889946APending Publication Date: 2025-04-25SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510118533.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Ni-molybdenum bimetallic phosphides have structural instability and agglomeration problems at fast charge and discharge rates, resulting in poor rate capability and electrochemical stability, which cannot meet the needs of flexible supercapacitor positive electrode materials.

Method used

By growing cobalt-doped nickel-molybdenum bimetallic oxide in situ on the carbon cloth and converting it into cobalt-doped nickel-molybdenum bimetallic phosphide by high-temperature phosphating method, a network structure is formed to improve the conductivity and cyclic stability of the material.

Benefits of technology

It achieves a longer cycle life and better charge and discharge performance, improves the rate performance and electrochemical stability of nickel-molybdenum bimetallic phosphides, and is suitable for flexible supercapacitor positive electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889946A_ABST
    Figure CN119889946A_ABST
Patent Text Reader

Abstract

The invention discloses a cobalt-doped nickel-molybdenum bimetallic phosphide grown on carbon cloth in situ and a preparation method and application thereof, and belongs to the field of preparation of flexible supercapacitor electrode materials, the method is characterized in that a cobalt-doped nickel molybdate hydrate is grown on carbon cloth through a hydrothermal method to obtain a cobalt-doped nickel molybdate hydrate / carbon cloth composite material, and the cobalt-doped nickel molybdate hydrate / carbon cloth composite material is used for preparing the flexible supercapacitor electrode materials. Annealing the cobalt-doped nickel molybdate hydrate / carbon cloth composite material in an oxygen-free environment to obtain a cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material; the cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material and red phosphorus are subjected to heat preservation treatment in an oxygen-free atmosphere at the temperature of 650-750 DEG C according to the mass ratio of 100: (50-400), the cobalt-doped nickel-molybdenum bimetallic phosphide growing on the carbon cloth in situ is obtained, high specific capacity can be achieved, and the cycling stability and the rate capability of the nickel-molybdenum bimetallic phosphide are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of flexible supercapacitor electrode material preparation, and specifically relates to a cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on a carbon cloth, and a preparation method and application thereof. Background Art

[0002] Flexible supercapacitors are energy storage devices with advantages such as long cycle life and high power density. They are considered to be one of the most promising energy storage technologies and can be better applied to wearable electronic devices. This flexible supercapacitor has flexibility requirements for electrode materials. Directly constructing active materials on conductive substrates can better meet the flexibility requirements. Conductive substrates include carbon cloth, nickel foam, etc. In order to explore and apply flexible supercapacitor technology, it is critical to develop new electrode materials and optimize production processes.

[0003] Transition metal phosphide materials have high conductivity, large theoretical capacity and metal-like properties, and are widely used battery electrode materials. Among them, transition bimetallic phosphides are represented by nickel-cobalt bimetallic phosphides. The synergistic effect between multiple metal elements helps to improve the conductivity of the material, so that the transition bimetallic phosphide shows better performance in electrochemical applications, and shows good stability in long-term electrochemical cycles, which is suitable for long-life electrochemical energy storage devices. The electrochemical properties of the material can be further improved by ion doping. Different ion doping improves the performance differently. Currently, the main doping in nickel-cobalt bimetallic phosphides is iron ion and magnesium ion. Ion doping can optimize the performance of nickel-molybdenum bimetallic phosphide from the following three aspects: first, it will change the lattice structure of nickel-molybdenum bimetallic phosphide, thereby increasing its conductivity; second, it will optimize the ion diffusion channels in nickel-molybdenum bimetallic phosphide, so that the relevant ions can diffuse more smoothly in the material, which helps to maintain a high ion transfer rate during rapid charging and discharging, thereby improving the rate performance; third, it will increase the number of active sites in the material, and these active sites can participate in electrochemical reactions more effectively. Under high-rate charge and discharge conditions, more active sites mean higher reaction rates and better rate performance.

[0004] However, nickel-molybdenum bimetallic phosphides have problems such as structural instability and agglomeration at fast charge and discharge rates, and therefore exhibit poor rate capability and electrochemical stability. Currently, the rate capability and electrochemical stability are mainly improved by combining reduced graphene oxide (rGO) with nickel-molybdenum bimetallic phosphides. However, this method usually involves multiple steps and complex chemical reactions, including the preparation of reduced graphene oxide, the synthesis of nickel-molybdenum bimetallic phosphides, and the combination of the two, which increases the complexity and cost of the preparation and requires strict control of the reaction conditions. The cycle life and charge and discharge performance still cannot meet the current needs of flexible supercapacitor positive electrode materials. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on carbon cloth and a preparation method and application thereof, which are simple and convenient to operate with low cost, so as to solve the problem that the cycle life and charge-discharge performance of nickel-molybdenum bimetallic phosphide still cannot meet the needs of current flexible supercapacitor positive electrode materials. The conductive performance is improved by cobalt doping and in-situ growth of nickel-molybdenum phosphide on carbon cloth, thereby achieving a longer cycle life and better charge-discharge performance.

[0006] The present invention is achieved through the following technical solutions: A method for preparing cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on carbon cloth comprises the following steps: S1, growing cobalt-doped nickel molybdate hydrate on carbon cloth by a hydrothermal method to obtain a cobalt-doped nickel molybdate hydrate / carbon cloth composite material, and then annealing the cobalt-doped nickel molybdate hydrate / carbon cloth composite material in an oxygen-free environment to obtain a cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material; S2, heat-treating the cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material and red phosphorus at a mass ratio of 100:(50-400) at 650-750° C. in an oxygen-free atmosphere to obtain a cobalt-doped nickel-molybdenum bimetallic phosphide in situ grown on the carbon cloth.

[0007] A further improvement of the present invention is: S1 obtains the cobalt-doped nickel molybdate hydrate / carbon cloth composite material according to the following process: Dissolving cobalt nitrate hexahydrate, nickel nitrate hexahydrate and sodium molybdate dihydrate in deionized water at a molar ratio of (0.2-0.6):(1-2):(1-2) to obtain a mixed solution; The acid-washed carbon cloth is placed in the mixed solution, and then maintained at 140-220° C. for 12-24 hours. The obtained carbon cloth is washed and dried to obtain a cobalt-doped nickel molybdate hydrate / carbon cloth composite material.

[0008] The obtained carbon cloth is washed with deionized water and ethanol, and then dried at 60-70° C. for 12-24 hours to obtain a cobalt-doped nickel molybdate hydrate / carbon cloth composite material.

[0009] The carbon cloth after the acid washing treatment is obtained by the following process: The carbon cloth is soaked in a mixture of concentrated nitric acid and concentrated sulfuric acid for 65-75 hours, wherein the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 3:1, then washed with deionized water until neutral, and dried at 60-70°C for 12-24 hours to obtain the acid-washed carbon cloth.

[0010] S1 obtains the cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material according to the following process: The cobalt-doped nickel molybdate hydrate / carbon cloth composite material is kept at 350-450° C. for 2-4 hours in a nitrogen atmosphere to obtain a cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material.

[0011] S2: The cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material is kept at 650-750° C. for 2-4 hours in a nitrogen atmosphere to obtain a cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth.

[0012] Red phosphorus and cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material are placed in two porcelain boats respectively. The porcelain boat with red phosphorus is placed upstream of the tubular furnace, and the porcelain boat with cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material is placed downstream of the tubular furnace. Then, the mixture is kept warm at 650-750°C for 2-4h to obtain cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth.

[0013] S1: heating the cobalt-doped nickel molybdate hydrate / carbon cloth composite material from room temperature to 350-450°C, and then keeping the temperature, with a heating rate of 5-10°C / min; S2 raises the temperature of the cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material from room temperature to 650-750°C, and then keeps the temperature, with a heating rate of 2-5°C / min.

[0014] A method for preparing cobalt-doped nickel-molybdenum bimetallic phosphide in-situ grown on carbon cloth as described in any of the above items, wherein the cobalt-doped nickel-molybdenum bimetallic phosphide in-situ grown on carbon cloth is obtained.

[0015] In situ grown cobalt-doped nickel-molybdenum bimetallic phosphide on carbon cloth for use as a positive electrode material for flexible supercapacitors.

[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention provides a preparation method of cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on carbon cloth. Cobalt-doped nickel molybdate hydrate can be grown on carbon cloth by a hydrothermal method. Then, cobalt-doped nickel molybdate hydrate can be converted into cobalt-doped nickel-molybdenum bimetallic oxide by annealing in an oxygen-free environment to obtain a precursor cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material. Finally, cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material and red phosphorus are heat-insulated in an oxygen-free atmosphere at 650-750° C. by a one-step high-temperature phosphating method to form cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on carbon cloth. Cobalt-doped nickel-molybdenum bimetallic phosphide presents a network structure. Metal cobalt ions are introduced into the nickel-molybdenum phosphide / carbon cloth composite material system, which can be used as a positive electrode material for a flexible supercapacitor. Cobalt ions provide a lot of stability and stimulate the self-activation function of the electrode material. Nickel and molybdenum ions also provide a lot of specific capacity. The present invention can achieve a higher specific capacity by adjusting the nickel-molybdenum ratio and the doping amount of metal cobalt ions, and improves the cycle stability and rate performance of the nickel-molybdenum bimetallic phosphide. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is an X-ray diffraction (XRD) diagram of the cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth prepared in Example 1.

[0018] Figure 2 These are scanning electron microscope (SEM) images of the cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth prepared in Example 1 at different magnifications.

[0019] Figure 3 The cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth prepared in Example 1 has a current density of 1-10 mA cm in a three-electrode system. -1 The charge and discharge curve (GCD) within the range.

[0020] Figure 4 The cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth prepared in Example 1 has a current density of 15 mA cm in the three-electrode system. -1 Long cycle performance diagram.

[0021] Figure 5 The current density of the in-situ grown nickel-molybdenum bimetallic phosphide on the carbon cloth in the three-electrode system is 1-10 mA cm -1 GCD graph within range.

[0022] Figure 6 The current density of the in-situ grown nickel-molybdenum bimetallic phosphide on the carbon cloth in the three-electrode system is 15 mA cm -1 Long cycle performance diagram. DETAILED DESCRIPTION

[0023] In order to more clearly illustrate the present invention, further description is given by implementing examples. The following examples do not limit the scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0024] The present invention provides a method for preparing a cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on a carbon cloth, comprising the following steps: 0.2-0.6 mmol of cobalt nitrate hexahydrate, 1-2 mmol of nickel nitrate hexahydrate, and 1-2 mmol of sodium molybdate dihydrate are dissolved in 30 mL of deionized water to obtain a mixed solution.

[0025] At the same time, the carbon cloth was soaked in a mixture of 60 mL of concentrated nitric acid (mass fraction 68%) and 20 mL of concentrated sulfuric acid for 72 hours. The carbon cloth area was 1 cm 2 , then washed with deionized water until neutral, and dried at 60-70°C for 12-24 hours to obtain the carbon cloth after acid washing, thereby increasing the hydrophilicity of the carbon cloth surface and allowing the precursor to grow evenly and in large quantities on the carbon cloth fibers.

[0026] Subsequently, the acid-washed carbon cloth is placed in solution A, and then transferred as a whole to a hydrothermal reactor with a polytetrafluoroethylene liner, and maintained at 140-220° C. for 12-24 hours. The obtained carbon cloth is washed with deionized water and ethanol, and then dried at 60-70° C. for 12-24 hours to obtain a cobalt-doped nickel molybdate hydrate / carbon cloth composite material.

[0027] Subsequently, the cobalt-doped nickel molybdate hydrate / carbon cloth composite material is heated from room temperature to 350-450°C at a heating rate of 5-10°C / min, and kept warm for 2-4 hours under a nitrogen atmosphere to obtain a cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material.

[0028] Red phosphorus and cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite materials are placed in two porcelain boats respectively. The porcelain boat containing 12.5-100 mg of red phosphorus is placed upstream of the tubular furnace, and the porcelain boat containing 25 mg of cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite materials is placed downstream of the tubular furnace. The temperature is raised from room temperature to 650-750°C and kept in a nitrogen atmosphere for 2-4 hours at a heating rate of 2-5°C / min to obtain cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth.

[0029] Embodiment 1: 0.4 mmol of cobalt nitrate hexahydrate, 1 mmol of nickel nitrate hexahydrate, and 1 mmol of sodium molybdate dihydrate were dissolved in 30 mL of deionized water to obtain solution A. At the same time, the carbon cloth was soaked in a mixed solution of 60 mL of concentrated nitric acid and 20 mL of concentrated sulfuric acid for 72 hours, then washed with deionized water until neutral, and dried at 70°C for 12 hours to obtain the carbon cloth after acid washing. Subsequently, the carbon cloth after acid washing was placed in solution A, transferred to a hydrothermal reactor with a polytetrafluoroethylene liner, and kept at 200°C for 16 hours. The obtained carbon cloth was washed with deionized water and ethanol, and then the obtained carbon cloth was dried at 70°C for 12 hours to obtain a cobalt-doped nickel molybdate hydrate / carbon cloth composite material.

[0030] Subsequently, the cobalt-doped nickel molybdate hydrate / carbon cloth composite material was heated from room temperature to 450°C at a heating rate of 5°C / min and kept warm for 2 hours in a nitrogen atmosphere to obtain a cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material.

[0031] Red phosphorus and cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material were placed in two porcelain boats respectively. The porcelain boat with 75 mg of red phosphorus was placed upstream of the tubular furnace, and the porcelain boat with 25 mg of cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material was placed downstream of the tubular furnace. The temperature was raised from room temperature to 750°C and kept for 2 hours under a nitrogen atmosphere at a heating rate of 4°C / min to obtain cobalt-doped nickel-molybdenum bimetallic phosphide in situ grown on the carbon cloth, which was recorded as Co-NMP / CC.

[0032] See also Figure 1 , Figure 1 This is the X-ray diffraction (XRD) pattern of the cobalt-doped nickel-molybdenum bimetallic phosphide in-situ grown on the carbon cloth prepared in Example 1, and its characteristic diffraction peak corresponds to nickel molybdenum phosphide (PDF#04-008-7245), indicating that the cobalt-doped nickel-molybdenum bimetallic phosphide in-situ grown on the carbon cloth has nickel molybdenum phosphide as the main phase.

[0033] See also Figure 2 , Figure 2 is a scanning electron microscope (SEM) image of the cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth prepared in Example 1. Figure 2 It can be seen that the cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth presents a network structure.

[0034] The cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth obtained in Example 1 was subjected to electrochemical testing in a three-electrode system, with a reference electrode being a mercury / mercuric oxide electrode, a counter electrode being a platinum sheet electrode, and an electrolyte being 4 mol L -1 of potassium hydroxide solution.

[0035] See also Figure 3 , Figure 3The cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth prepared in Example 1 has a current density of 1-10 mA cm in a three-electrode system. -1 The charge-discharge curve (GCD) in the range of 1 mA cm shows a high specific capacity at all current densities. -1 At a current density of , the specific capacity is 757.66mFcm -2 At current densities of 2, 3, 5, and 10 mA cm -1 When the specific capacities are 773.68, 743.46, 697.00, and 604.00 mFcm -2 The rate performance is 79.72%.

[0036] See also Figure 4 , Figure 4 The cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth prepared in Example 1 was subjected to 15 mA cm -1 After 5000 cycles at a current density of , the cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth still has a capacity retention rate of 84.05%.

[0037] Comparison example: 1 mmol of nickel nitrate hexahydrate and 1 mmol of sodium molybdate dihydrate were dissolved in 30 mL of deionized water to obtain solution B. At the same time, the carbon cloth was soaked in a mixture of 60 mL of concentrated nitric acid and 20 mL of concentrated sulfuric acid for 72 hours, then washed with deionized water until neutral, and dried at 70°C for 12 hours to obtain the carbon cloth after acid washing. Subsequently, the carbon cloth after acid washing was placed in solution B, transferred to a hydrothermal reactor with a polytetrafluoroethylene liner, and kept at 200°C for 16 hours. The obtained carbon cloth was washed with deionized water and ethanol, and then the obtained carbon cloth was dried at 70°C for 12 hours to obtain a nickel molybdate hydrate / carbon cloth composite material.

[0038] Subsequently, the nickel molybdate hydrate / carbon cloth composite material was heated from room temperature to 450°C at a heating rate of 5°C / min and kept warm for 2 hours under a nitrogen atmosphere to obtain a nickel-molybdenum bimetallic oxide / carbon cloth composite material.

[0039] Red phosphorus and nickel-molybdenum bimetallic oxide / carbon cloth composite material were placed in two porcelain boats respectively. The porcelain boat containing 75 mg of red phosphorus was placed upstream of the tubular furnace, and the porcelain boat containing 25 mg of nickel-molybdenum bimetallic oxide / carbon cloth composite material was placed downstream of the tubular furnace. The temperature was raised from room temperature to 750°C and kept for 2 hours under a nitrogen atmosphere at a heating rate of 4°C / min to obtain nickel-molybdenum bimetallic phosphide in situ grown on the carbon cloth, which was recorded as NMP / CC.

[0040] The test process of the in-situ grown nickel-molybdenum bimetallic phosphide on the carbon cloth in the three-electrode system is the same as that of Example 1, except that the sample of Example 1 is replaced by the sample of the control example, see Figure 5 , at 1mAcm -1 At a current density of , the specific capacity is 451.20mFcm -2 At current densities of 2, 3, 5, and 10 mA cm -1 When the specific capacities are 416.44, 393.60, 359.00, and 306.00 mFcm -2 The rate performance is 67.82%, and both the specific capacity and rate performance are lower than those of the cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on carbon cloth.

[0041] See also Figure 6 , Figure 6 The current density of the NiMo bimetallic phosphide grown in situ on carbon cloth in the three-electrode system is 15 mA cm -1 Long cycle performance diagram. After 5000 cycles, the capacity retention rate of the control sample is 16.26%, which is much lower than that of the cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on carbon cloth.

[0042] Embodiment 2: 0.2 mmol of cobalt nitrate hexahydrate, 1 mmol of nickel nitrate hexahydrate, and 1 mmol of sodium molybdate dihydrate were dissolved in 30 mL of deionized water to obtain solution C. At the same time, the carbon cloth was soaked in a mixture of 60 mL of concentrated nitric acid and 20 mL of concentrated sulfuric acid for 72 hours, then washed with deionized water until neutral, and dried at 70°C for 12 hours to obtain an acid-washed carbon cloth. Subsequently, the acid-washed carbon cloth was placed in solution C and transferred to a hydrothermal reactor with a polytetrafluoroethylene liner, kept at 200°C for 16 hours, and the obtained carbon cloth was washed with deionized water and ethanol, and then the obtained carbon cloth was dried at 70°C for 12 hours to obtain a cobalt-doped nickel molybdate hydrate / carbon cloth composite material.

[0043] Subsequently, the cobalt-doped nickel molybdate hydrate / carbon cloth composite material was heated from room temperature to 450°C at a heating rate of 5°C / min and kept warm for 2 hours in a nitrogen atmosphere to obtain a cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material.

[0044] Red phosphorus and cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material were placed in two porcelain boats respectively. The porcelain boat containing 75 mg of red phosphorus was placed upstream of the tubular furnace, and the porcelain boat containing 25 mg of cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material was placed downstream of the tubular furnace. The temperature was raised from room temperature to 750°C and kept for 2 hours under a nitrogen atmosphere at a heating rate of 4°C / min to obtain cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth.

[0045] Embodiment 3: 0.4 mmol of cobalt nitrate hexahydrate, 1 mmol of nickel nitrate hexahydrate, and 1 mmol of sodium molybdate dihydrate were dissolved in 30 mL of deionized water to obtain solution A. At the same time, the carbon cloth was soaked in a mixed solution of 60 mL of concentrated nitric acid and 20 mL of concentrated sulfuric acid for 72 hours, then washed with deionized water until neutral, and dried at 70°C for 12 hours to obtain the carbon cloth after acid washing. Subsequently, the carbon cloth after acid washing was placed in solution A, transferred to a hydrothermal reactor with a polytetrafluoroethylene liner, and kept at 200°C for 16 hours. The obtained carbon cloth was washed with deionized water and ethanol, and then the obtained carbon cloth was dried at 70°C for 12 hours to obtain a cobalt-doped nickel molybdate hydrate / carbon cloth composite material.

[0046] Subsequently, the cobalt-doped nickel molybdate hydrate / carbon cloth composite material was heated from room temperature to 450°C at a heating rate of 5°C / min and kept warm for 2 hours in a nitrogen atmosphere to obtain a cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material.

[0047] Red phosphorus and cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite materials were placed in two porcelain boats respectively. The porcelain boat containing 100 mg of red phosphorus was placed upstream of the tubular furnace, and the porcelain boat containing 25 mg of cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite materials was placed downstream of the tubular furnace. The temperature was raised from room temperature to 750°C and kept for 2 hours under a nitrogen atmosphere at a heating rate of 4°C / min to obtain cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth.

[0048] Embodiment 4: 0.4 mmol of cobalt nitrate hexahydrate, 1 mmol of nickel nitrate hexahydrate, and 1 mmol of sodium molybdate dihydrate were dissolved in 30 mL of deionized water to obtain solution A. At the same time, the carbon cloth was soaked in a mixed solution of 60 mL of concentrated nitric acid and 20 mL of concentrated sulfuric acid for 72 hours, then washed with deionized water until neutral, and dried at 70°C for 12 hours to obtain the carbon cloth after acid washing. Subsequently, the carbon cloth after acid washing was placed in solution A, transferred to a hydrothermal reactor with a polytetrafluoroethylene liner, and kept at 200°C for 16 hours. The obtained carbon cloth was washed with deionized water and ethanol, and then the obtained carbon cloth was dried at 70°C for 12 hours to obtain a cobalt-doped nickel molybdate hydrate / carbon cloth composite material.

[0049] Subsequently, the cobalt-doped nickel molybdate hydrate / carbon cloth composite material was heated from room temperature to 450°C at a heating rate of 5°C / min and kept warm for 2 hours in a nitrogen atmosphere to obtain a cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material.

[0050] Red phosphorus and cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material were placed in two porcelain boats respectively. The porcelain boat containing 75 mg of red phosphorus was placed upstream of the tubular furnace, and the porcelain boat containing 25 mg of cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material was placed downstream of the tubular furnace. The temperature was raised from room temperature to 750°C and kept for 2 hours under a nitrogen atmosphere at a heating rate of 2°C / min to obtain cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth.

[0051] Embodiment 5: 0.4 mmol of cobalt nitrate hexahydrate, 1 mmol of nickel nitrate hexahydrate, and 1 mmol of sodium molybdate dihydrate were dissolved in 30 mL of deionized water to obtain solution A. At the same time, the carbon cloth was soaked in a mixed solution of 60 mL of concentrated nitric acid and 20 mL of concentrated sulfuric acid for 72 hours, then washed with deionized water until neutral, and dried at 70°C for 12 hours to obtain the carbon cloth after acid washing. Subsequently, the carbon cloth after acid washing was placed in solution A and transferred to a hydrothermal reactor with a polytetrafluoroethylene liner, kept at 140-220°C for 16 hours, and the obtained carbon cloth was washed with deionized water and ethanol, and then the obtained carbon cloth was dried at 70°C for 12 hours to obtain a cobalt-doped nickel molybdate hydrate / carbon cloth composite material.

[0052] Subsequently, the cobalt-doped nickel molybdate hydrate / carbon cloth composite material was heated from room temperature to 450°C at a heating rate of 5°C / min and kept warm for 2 hours in a nitrogen atmosphere to obtain a cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material.

[0053] Red phosphorus and cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material were placed in two porcelain boats respectively. The porcelain boat containing 75 mg of red phosphorus was placed upstream of the tubular furnace, and the porcelain boat containing 25 mg of cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material was placed downstream of the tubular furnace. The temperature was raised from room temperature to 750°C and kept for 2 hours under a nitrogen atmosphere at a heating rate of 4°C / min to obtain cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth.

[0054] In the in-situ grown cobalt-doped nickel-molybdenum bimetallic phosphide on the carbon cloth prepared in Example 5, the main phase can be phosphated to nickel-molybdenum phosphide regardless of the temperature at which the precursor is produced within the range of 140-220°C.

Claims

1. A method for preparing cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on carbon cloth, characterized in that: The following steps are involved: S1, growing cobalt-doped nickel molybdate hydrate on carbon cloth by a hydrothermal method to obtain a cobalt-doped nickel molybdate hydrate / carbon cloth composite material, and then annealing the cobalt-doped nickel molybdate hydrate / carbon cloth composite material in an oxygen-free environment to obtain a cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material; S2, heat-treating the cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material and red phosphorus at a mass ratio of 100:(50-400) at 650-750° C. in an oxygen-free atmosphere to obtain a cobalt-doped nickel-molybdenum bimetallic phosphide in situ grown on the carbon cloth.

2. The method for preparing the in-situ grown cobalt-doped nickel-molybdenum bimetallic phosphide on carbon cloth according to claim 1, characterized in that: S1 obtains the cobalt-doped nickel molybdate hydrate / carbon cloth composite material according to the following process: Dissolving cobalt nitrate hexahydrate, nickel nitrate hexahydrate and sodium molybdate dihydrate in deionized water at a molar ratio of (0.2-0.6):(1-2):(1-2) to obtain a mixed solution; The acid-washed carbon cloth is placed in the mixed solution, and then maintained at 140-220° C. for 12-24 hours. The obtained carbon cloth is washed and dried to obtain a cobalt-doped nickel molybdate hydrate / carbon cloth composite material.

3. The method for preparing the in-situ grown cobalt-doped nickel-molybdenum bimetallic phosphide on carbon cloth according to claim 2, characterized in that: The obtained carbon cloth is washed with deionized water and ethanol, and then dried at 60-70° C. for 12-24 hours to obtain a cobalt-doped nickel molybdate hydrate / carbon cloth composite material.

4. The method for preparing the in-situ grown cobalt-doped nickel-molybdenum bimetallic phosphide on carbon cloth according to claim 2, characterized in that: The carbon cloth after the acid washing treatment is obtained by the following process: The carbon cloth is soaked in a mixture of concentrated nitric acid and concentrated sulfuric acid for 65-75 hours, wherein the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 3:1, then washed with deionized water until neutral, and dried at 60-70°C for 12-24 hours to obtain the acid-washed carbon cloth.

5. The method for preparing the in-situ grown cobalt-doped nickel-molybdenum bimetallic phosphide on carbon cloth according to claim 1, characterized in that: S1 obtains the cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material according to the following process: The cobalt-doped nickel molybdate hydrate / carbon cloth composite material is kept at 350-450° C. for 2-4 hours in a nitrogen atmosphere to obtain a cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material.

6. The method for preparing the cobalt-doped nickel-molybdenum bimetallic phosphide in-situ grown on carbon cloth according to claim 5, characterized in that: S2: The cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material is kept at 650-750° C. for 2-4 hours in a nitrogen atmosphere to obtain a cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth.

7. The method for preparing the cobalt-doped nickel-molybdenum bimetallic phosphide in-situ grown on carbon cloth according to claim 6, characterized in that: Red phosphorus and cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material are placed in two porcelain boats respectively. The porcelain boat with red phosphorus is placed upstream of the tubular furnace, and the porcelain boat with cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material is placed downstream of the tubular furnace. Then, the mixture is kept warm at 650-750°C for 2-4h to obtain cobalt-doped nickel-molybdenum bimetallic phosphide grown in situ on the carbon cloth.

8. The method for preparing cobalt-doped nickel-molybdenum bimetallic phosphide in-situ grown on carbon cloth according to claim 6, characterized in that: S1: heating the cobalt-doped nickel molybdate hydrate / carbon cloth composite material from room temperature to 350-450°C, and then keeping the temperature, with a heating rate of 5-10°C / min; S2 raises the temperature of the cobalt-doped nickel-molybdenum bimetallic oxide / carbon cloth composite material from room temperature to 650-750°C, and then keeps the temperature, with a heating rate of 2-5°C / min.

9. A cobalt-doped nickel-molybdenum bimetallic phosphide in situ grown on carbon cloth prepared by the method for preparing cobalt-doped nickel-molybdenum bimetallic phosphide in situ grown on carbon cloth according to any one of claims 1 to 8.

10. Use of the cobalt-doped nickel-molybdenum bimetallic phosphide in-situ grown on carbon cloth as claimed in claim 9 in a positive electrode material for a flexible supercapacitor.